2018
DOI: 10.1016/j.econedurev.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Test scores, noncognitive skills and economic growth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 86 publications
1
19
0
1
Order By: Relevance
“…For example, Borghans and Schils (2015) have shown that PISA scores can be used to measure non-cognitive abilities of students, such as "agreeableness, and motivational attitudes toward learning" and those studies are predictive of the success of those students later in life. Balart et al (2015) in fact show that those same abilities, picked up indirectly through PISA test scores, are predictive of national GDP growth. More generally, Heckman and his co-authors (see, e.g., Cunha et al 2010) have extensively shown that non-cognitive abilities, hitherto thought difficult to measure, 35 are as important or more as traditional cognitive abilities in determining the human capital of a population.…”
Section: Concluding Discussionmentioning
confidence: 84%
“…For example, Borghans and Schils (2015) have shown that PISA scores can be used to measure non-cognitive abilities of students, such as "agreeableness, and motivational attitudes toward learning" and those studies are predictive of the success of those students later in life. Balart et al (2015) in fact show that those same abilities, picked up indirectly through PISA test scores, are predictive of national GDP growth. More generally, Heckman and his co-authors (see, e.g., Cunha et al 2010) have extensively shown that non-cognitive abilities, hitherto thought difficult to measure, 35 are as important or more as traditional cognitive abilities in determining the human capital of a population.…”
Section: Concluding Discussionmentioning
confidence: 84%
“…Test performance is highly correlated with both individual income and economic growth, but explains little of the variation in income across individuals in the U.S., and particularly under-predicts U.S. economic growth in cross-country comparisons (Murnane et al, 2000;Hanushek and Woessmann, 2011). Differences in test-taking effort across students and across cultures may add explanatory power to these analyses and better inform our understanding of the relationship between ability and long-term outcomes (e.g., Borghans and Schils, 2013;Balart et al, 2015;Segal, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that scores on low-stakes tests do not always reflect students' true ability has already been recognized in the literature (Wise and DeMars 2005 and Finn 2015 provide reviews). One strand of research uses observational data to examine correlations between performance and proxies for motivation and effort, including self-reported motivation, interest, attitudes and effort, fast response times, low item response rates, and declining performance over the course of the test (e.g., Eklöf 2010; DeMars and Wise 2010; Borghans and Schils 2013; Zamarro, Hitt, and Mendez 2016;Borgonovi and Biecek 2016;Balart, Oosterveen, and Webbink 2017;Akyol, Krishna, and Wang 2018). 3 Yet, important for our purposes, these studies are not able to identify the impact of effort separately from the impact of ability.…”
Section: Background Literaturementioning
confidence: 99%